Cycling‐specific isometric resistance training improves peak power output in elite sprint cyclists. (29th June 2020) - Kordi, Mehdi; Folland, Jonathan P; Goodall, Stuart; Menzies, Campbell; Patel, Tejal Sarika; Evans, Martin; Thomas, Kevin; Howatson, Glyn
Abstract : Introduction: This study aimed to assess the efficacy of a 6‐week cycling‐specific, isometric resistance training program on peak power output (PPO) in elite cyclists. Methods: Twenty‐four elite track sprint cyclists were allocated to EXP (n = 13, PPO, 1537 ± 307 W) and CON (n = 11, PPO, 1541 ± 389 W) groups. All participants completed a 6‐week training program; training content was identical except participants in the EXP group replaced their usual compound lower body resistance training exercise with a cycling‐specific, isometric resistance training stimulus. Cycling PPO, knee extensor and cycling‐specific isometric strength, and measures of muscle architecture were assessed pre‐ and post‐training. Results: In EXP, absolute and relative PPO increased (46 ± 62 W and 0.8 ± 0.7 W/kg, P < .05), and the change in relative PPO was different to CON (−0.1 ± 1.0 W/kg, group × time interaction P = .02). The increase in PPO was concurrent with an increase in extrapolated maximal torque in EXP (7.1 ± 6.5 Nm, P = .007), but the effect was not different from the change in CON (2.4 ± 9.7 Nm, group × time P = .14). Cycling‐specific isometric strength also increased more in EXP (group × time P = .002). There were no other between‐group differences in response to training. Conclusion: A 6‐week novel, cycling‐specific isometric resistance training period improved PPO in a group of elite sprint cyclists by 3%‐4%. These data support the use of a cycling‐specific isometric resistance training stimulus in the preparation programs of world‐class cyclists.